Ethical obstacles of cross-cultural communication in global society - Ekadumov, Andrew I. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Community’s ability for cross-cultural synthesis in the situation of multi-cultural globality is defined by the type of ethical sysmem described in the conception of V. A. Lefevr that prevailes in it. Ethics that enforces bans makes more opportunity for productive cross-cultural dialogue in comparison with the ethics that obliges one for the realization of good. Global modernity provokes more severe aftermath in societies with ethic systems declaring good than in societies committed to ethics of prohibitions. Traditional moral conduct increasingly gives way to the need for a conscious individual choice in a unique situation. In an overabundance of cultural codes such a choice is more problematic for adherents of an ethical system that requires conformity to the ideal pattern of good, than to for adherents of an ethics prohibiting perpetration of evil.